PERANCANGAN INTERFACE SISTEM INFORMASI PENDAFTARAN PADA TAMAN KANAK-KANAK AS-SALAM BERBASIS WEB: Registration, Website, HTML, PHP - Susanto, Darex; Bagus, Kukuh Idgam; Shanata, Raisa; Angga Sari, Anisa Putri (FORTECH (Journal of Information Technology), 2025)
Every year the school always carries out a process of accepting new students select prospective students who will register. As-Salam Kindergarten is one of the schools is in Jambi which accepts new students. In the registration process carried out As - Salam Kindergarten still uses manual methods, namely still using brochures and paper forms. This can cause several problems, namely data loss and take a long time Enter the data contained in the form. From these problems, an information system is needed registration which can reduce obstacles that might occur in the previous system. System registration information contains the registration process starting from providing registration information, filling out the form, checking data, and reporting selection results in the form of a website application. In creating a website you will using HTML and PHP. Results of research on the registration information system at the As - Salam based Kindergarten This website can simplify and help in the registration process.